Subprodutos das indústrias madeireiras como matéria-prima para produção de MDP - Natalli, Luiz Henrique (2020)
The timber industries generate significant amounts of waste and / or by-products that require alternatives for reuse, in addition to those already used, in order to add value to materials with potential for use. This study aimed to verify the technical potential of using waste from the timber industries as a raw material for the production of MDP (Medium Density Particleboard). Through the application of a questionnaire, a diagnosis was made of the main residues generated by the wood industries in the regions of Guarapuava and Irati, Paraná. The by-products considered promising were from the veneer and plywood panel industries, being selected for study “log core”, “veneer clippings” and “plywood cutting” the types named in this study. The MDP panels were produced with urea-formaldehyde adhesive and a nominal specific gravity of 650 kg / m³, using pure or mixture by-products and a type of panel produced with industrially particles. The panel's physical-mechanical properties were evaluated by comparing them to the requirements of international standards, by analysis of variance and by the mixture modeling method. It was verified that the panels produced with “log core” and “veneer clippings” residues showed satisfactory results with similar physical properties and higher mechanical properties of perpendicular tensile strength and screw withdrawal. The panels produced with these by-products did not reach all international requirements, but they that can be improved with adjustments in the production process. The panels produced with “plywood cutting” presented unsatisfactory mechanical properties, which was attributed to the presence of cured phenol-formaldehyde resin in the wood. Therefore, it can be concluded that the "log core" and "veneer clippings" residues types has the potential to be used in the composition of MDP.